The Horntail Snail (Macrochlamys indica): A New Invasive Pest in Florida - Alexandra M. Revynthi; Daniel Carrillo; Dakshina Seal; Vanessa E. Vassilaros; Paul E. Kendra (EDIS)
The horntail snail was detected, in August 2020, in Miami-Dade County. This snail is considered of quarantine importance in the United States because it can become an agricultural pest and potentially host parasitic nematodes of medical significance. A program to survey, control, and eradicate the horntail snail has been implemented by the Florida Department of Agriculture and Consumer Services, Division of Plant Industry.